Epigenetic modifications in neuropathic pain. (26th November 2021) - Luo, Danzhi; Li, Xiaohong; Tang, Simin; Song, Fuhu; Li, Wenjun; Xie, Guiling; Liang, Jinshu; Zhou, Jun
Neuropathic pain (NP) is a common symptom in many diseases of the somatosensory nervous system, which severely affects the patient's quality of life. Epigenetics are heritable alterations in gene expression that do not cause permanent changes in the DNA sequence. Epigenetic modifications can affect gene expression and function and can also mediate crosstalk between genes and the environment. Increasing evidence shows that epigenetic modifications, including DNA methylation, histone modification, non-coding RNA, and RNA modification, are involved in the development and maintenance of NP. In this review, we focus on the current knowledge of epigenetic modifications in the development and maintenance of NP. Then, we illustrate different facets of epigenetic modifications that regulate gene expression and their crosstalk. Finally, we discuss the burgeoning evidence supporting the potential of emerging epigenetic therapies, which has been valuable in understanding mechanisms and offers novel and potent targets for NP therapy.